Phytoplankton, trophic state and ecological potential in reservoirs in the State of São Paulo, Brazil - Rodrigues, Eduardo Henrique Costa [UNESP]; Vicentin, Aline Martins [UNESP]; Machado, Leila Dos Santos [UNESP]; Pompêo, Marcelo Luiz Martins; Carlos, Viviane Moschini [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2019)
This study evaluated the ecological potential of reservoirs in the Brazilian state of São Paulo, having phytoplankton as a biological quality element. Integrated water column sampling was carried out in the dam, and in the intermediate and fluvial zones of the Igaratá, Atibainha, Paiva Castro, Rio Grande, Itupararanga, Broa, Barra Bonita, Guarapiranga and Salto Grande reservoirs in July 2015. Physico-chemical and biological parameters were analyzed in all environments. The phytoplankton was analyzed under an inverted microscope, and measurements of density, diversity, equitability and dominance were determined. The data was ordered using PCA and CCA analysis. The ecological potential of the reservoirs was determined through the evenness index. The electrical conductivity, nitrate, nitrite and orthophosphate were higher in the more eutrophic reservoirs: Salto Grande, Barra Bonita, Guarapiranga and Rio Grande. A trophic gradient was observed among the sampling points, suggesting a conservation spectrum. There was dominance of cyanobacteria in the eutrophic reservoirs associated with low diversity and high dominance. The total density was correlated with TP, TN, and pH. A divergent relationship between the trophic state index and the evenness index was observed. The Atibainha, Itupararanga, Broa, Barra Bonita and Salto Grande reservoirs were classified as water bodies of very poor ecological quality (Bad). The evenness index seems to be a good alternative to the biomonitoring of the studied reservoirs.
Fitoplâncton, estado trófico e potencial ecológico em reservatórios do estado de São Paulo, Brasil
Keywords: Eutrophication; Pollution; Water quality